2022
DOI: 10.1002/jee.20456
|View full text |Cite
|
Sign up to set email alerts
|

The multiplicative function of expectancy and value in predicting engineering students' choice, persistence, and performance

Abstract: Background: Students are more likely to persist when they both perceive themselves as capable of success (expectancy) and perceive tasks to be interesting, important, and useful (values) or less costly in terms of effort, lost opportunities, and psychological stress (perceived costs). Prior research has not examined whether these motivational beliefs synergistically predict engineering-related outcomes; studying such synergy is critical for understanding how multiple forms of motivation combine to support engi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Yet, even if the decision to study a STEM subject has already been made, differences in STEM students' self-efficacy and value beliefs, e.g., due to their perceived minority status as a female or first-generation student, occur and should not be neglected, as they were shown to be relevant for study success [9,29,30]. For example, a study with a sample of first-year engineering undergraduates showed that higher levels of engineering self-efficacy and highly valuing engineering were related to higher engineering persistence [31].…”
Section: Expectancy and Value Beliefsmentioning
confidence: 99%
“…Yet, even if the decision to study a STEM subject has already been made, differences in STEM students' self-efficacy and value beliefs, e.g., due to their perceived minority status as a female or first-generation student, occur and should not be neglected, as they were shown to be relevant for study success [9,29,30]. For example, a study with a sample of first-year engineering undergraduates showed that higher levels of engineering self-efficacy and highly valuing engineering were related to higher engineering persistence [31].…”
Section: Expectancy and Value Beliefsmentioning
confidence: 99%
“…Expectancy-value theory predicts that students will put in more effort if they perceive value in a learning activity, which has been shown to be effective in encouraging active learning ( 8 ). By providing students with opportunities to engage with microbiology and immunology current events of their own choosing, students are expected to be intrinsically motivated to work harder, pursue more biology-based coursework in the future ( 9 ), and become better consumers of science-based news stories. This iterative series of activities uses expectancy-value theory by asking students to explain, using lay language, the relevance of course content to contemporary news events, all to increase student motivation.…”
Section: Introductionmentioning
confidence: 99%
“…This is an involved effort because students taking the same course can engage with it and experience it in different ways depending on the prior background that they bring with them to the course such as their motivation, sense of belonging and study resources. Researchers in Engineering education are working to identify such sets of student features that play a role in course performance Specifically, researchers studied whether aspects related to their motivation, such as expectancy to do well, is related to course outcomes [1,8,9], whether high performing students have different study behaviors than low performing students [10], and whether other sources such as sense of belonging and stress contributes to the struggles that students face [2]. This prior work mainly focused on first year Engineering courses.…”
Section: Introductionmentioning
confidence: 99%